Lessons from the Interagency Emergency Health Kit for access to essential medicines in Canada - Houston, Adam R; Nickerson, Jason W (Université d'Ottawa | University of Ottawa, 2019)
Abstract Despite Canada’s efforts to position itself as a global health leader, important medicines, including multiple drugs found on the WHO Model List of Essential Medicines, are not available domestically. Of the fourteen medicines found in the Interagency Emergency Health Kit, the most basic distillation of the global health toolkit designed for responding to acute humanitarian crises, only ten are currently sold in Canada; alternative treatments that are available may not be as effective or affordable. Their absence highlights broader issues with Canada’s market-driven system of access to medicines, with implications for the care of refugees and other populations, while serving as a reminder of the importance of ensuring access to essential medicines in all settings.